â€œGame Theory and Competitive Analyseâ€ for Developing the Turistic Priorities in Albanian Region. The Case Study of Vlora Coast. - Ramosacaj, Miftar; Dumi, Alba (Mediterranean Journal of Social Sciences, 2012)
In this article, consider optimal decision making in two-alternative forced-choice. The paper research consist byanalyzing the mathematical models of TAFC decision making and show that all but one can be reduced to the drift diffusionmodel, implementing the statistically optimal algorithm (most accurate for a given speed or fastest for a given accuracy). Thepaper research prove further that there is always an optimal trade-off between speed and accuracy that maximizes variousreward functions, including reward rate (percentage of correct responses per unit time), as well as several other objectivefunctions, including ones weighted for accuracy. These findings address empirical data and make novel predictions aboutperformance under optimality. This literature review of decision making (how people make choices among desirablealternatives), culled from the disciplines of psychology, economics, and mathematics, covers the theory of riskless choices, theapplication of the theory of riskless choices to welfare economics, the theory of risky choices, transitivity of choices, and thetheory of games and statistical decision functions. [1] [2] [3] In this paper we are trying to adopt the concrete data of ITC in Vloraregion for touristic promoting. The theories surveyed assume rational behavior: individuals have transitive preferences. Thereare two points of hypothesis in this study: 1.The GTCA (Game theory and competitive analyse) theory and it apply in Albaniancondition for promoting the tourism.2. MMDM (Mathematics Models and Decision Making) theory and apply in developing theconditions for promoting the reforming in Albania. Game theory, a discipline that was given its modern form by themathematician John von Neumann, models markets in which the actions of competing parties influence one another while eachacts in its own self interest.